Safety assessment of coleopteran active IPD072Aa protein from Pseudomonas chlororaphis. (July 2019) - Carlson, Anne B.; Mathesius, Carey A.; Ballou, Stephen; Boeckman, Chad J.; Gunderson, Tim A.; Mirsky, Henry P.; Mukerji, Pushkor; Roe, Jacqueline C.; Schmidt, Jean M.; Zhang, John; Delaney, Bryan
Abstract: The ipd072Aa gene from Pseudomonas chlororaphis encodes the IPD072Aa protein which confers protection against certain coleopteran pests when expressed in genetically modified (GM) plants. A weight of evidence approach was used to assess the safety of the IPD072Aa protein. This approach considered the history of safe use of the source organism and bioinformatic comparison of the protein sequence with known allergenic and toxic proteins. The IPD072Aa protein was assessed for resistance to degradation in the presence of simulated gastric fluid containing pepsin as well as heat stability. There was no hazard identified with the IPD072Aa protein. Furthermore, an acute oral toxicity study found no evidence of adverse effects. Collectively, these studies support the human health safety assessment of the IPD072Aa protein. Highlights: IPD072Aa is a novel insecticidal protein obtained from Pseudomonas chlororaphis active on certain Coleoptera. IPD072Aa protein in genetically modified maize offers a new mode of action of protection against western corn rootworm. A weight of evidence approach was used to assess the safety of the IPD072Aa protein. No toxin or allergen hazard was identified therefore the IPD072Aa protein is not expected to adversely impact human health.